A PRAYER OF ULU AL-AZM IN THE HOLE QUR’AN, A STUDY OF THE OBJECTIVITY OF IBRAHIM AND MOSES, PEACE BE UPON THEM, AS AN EXAMPLE (International Journal of Engineering Sciences & Management Research, 2021)
The origin of the word determination in linguistic form is due to intent and the holding of the heart's intention to do something and to realize the goal and the goal. Therefore, it is said to the man who is motivated and active and who seeks to achieve his goal: the one with determination, and steadfast determination: firm.